KESEHATAN REPRODUKSI PADA KURIKULUM MADRASAH DI SUMATERA SELATAN - Abdul Hadi (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2014)
Reproductive health curriculum that has yet to be fully implemented, especially in the madrasah whose numbers until now about 58,439 units all over Indonesia. The main reason has not been integrated reproductive health curriculum that still occurs due to the pro and contra opinions of the scholars about the boundaries and standards of teaching materials that will be taught. One local newspaper in Palembang featuring reader letters describes the concerns about the dangers of global development of adolescent reproductive health. Therefore knowledge about reproductive health must be given to teenagers so they do not fall in free sex, pregnancy outside marriage which would have a negative impact for families and communities.ملخص: مناهج الصحة الإنجابية التي لم تنفذ بالكامل، وخاصة في المدارس الدينية التي حتى الآن حوالي 58,439 وحدة في جميع أنحاء اندونيسيا الأرقام. السبب الرئيسي لم يتم دمج المناهج الصحة الإنجابية التي لا تزال تحدث بسبب الآراء المؤيدة وكونترا العلماء حول حدود ومعايير المواد التعليمية التي سيتم تدريسها. إحدى الصحف المحلية في باليمبانج يضم خطابات القارئ يصف المخاوف بشأن مخاطر التنمية العالمية للصحة الإنجابية للمراهقين. ولذلك يجب أن تعطى المعرفة حول الصحة الإنجابية للمراهقين حتى لا تقع في حرية ممارسة الجنس، والحمل خارج إطار الزواج مما سيكون له تأثير سلبي على الأسر والمجتمعات المحلية.